O językowych wykładnikach wartości w dawnej polszczyźnie = Linguistic value indicators in old Polish language - Cybulski, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents selected formal and linguistic value indicators relating to four important sets of definitions: God vs. devil; old, ancient vs. new and youth; familiarity vs. strangeness; greatness vs. tawdriness. The research material was gathered from old Polish, mainly non-literary texts.
Keywords: język polski; wykładniki wartości; 15-19 w.; Polish language; value indicators; 15th-19th century